Electro-elastic Lamb waves in dielectric plates. (September 2020) - Conroy Broderick, Hannah; Dorfmann, Luis; Destrade, Michel
Abstract: We study the propagation of Lamb waves in soft dielectric plates subject to mechanical and electrical loadings and find the explicit expressions for the dispersion equations in the cases of neo-Hookean and Gent dielectrics. We elucidate the effects of the electric field, of the thickness-to-wavelength ratio, of pre-stress and of strain-stiffening on the wave characteristics.